ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENYUSUNAN LAPORAN KEUANGAN PADA USAHA MIKRO, KECIL DAN MENENGAH (UMKM) DI KABUPATEN MELAWAI - Rahayu Widyawati; Aris Setiawan; Risal Risal (Jurnal Akuntansi dan Keuangan, 2022)
This research is motivated by the ignorance of Micro, Small and Medium Enterprises (MSME) actors in Melawi Regency about the accounting process and the difficulties in preparing financial reports properly or according to the applicable Financial Accounting Standards (SAK). The different education levels of MSME actors in Melawi Regency affect the knowledge and ability of MSME players in preparing financial reports. Some MSME actors in Melawi Regency tend to prepare financial reports when necessary and most of them think that the business they are running is still not big enough to compile a complete financial report. The purpose of this research is to analyze the factors of MSME actors in Melawi Regency in preparing financial statements. The method used is quantitative research methods with sampling techniques using simple random sampling. Data processing and analysis techniques used in this research are validity test, reliability test, classical assumption test and multiple regression test. The results of this study prove that the education level variable has a significant effect on the preparation of financial statements, the accounting training variable has a significant effect on the preparation of financial statements and the business scale has no effect on the preparation of financial statements. while simultaneously the variables of education level, accounting training and business scale have a significant effect on the preparation of financial statements.